An integrated counseling approach : Building harmony among psychology, spritituality, and community values - Eli Trisnowati, M.Pd; Novi Wahyu Hidayati (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
this article explors in integrated counseling approach that harmonizes psychological principles, spiritual dimensions, and community based values. in many educational and community settings, individuals face complex personal, emotional, and sosial challenges that cannot be addressed through a single theoretical lens. an ontegrated interventions, meaningful spiritual insights, and culturally noted communal norms. this promotes responsible social behavior. through a synthesis of literature and conceptual applications of integrated counseling. the findings emphasize that incorporating can enrich the counseling process and provide deeper support for clients in diverse sosiocultural contexts